1977
DOI: 10.1002/lary.5540870508
|View full text |Cite
|
Sign up to set email alerts
|

Malignant neoplasms of the nasal cavities and paranasal sinuses: (A retrospective study)

Abstract: This study presents a retrospective look at 115 patients evaluated here from 1957 to 1974. In this series, 57 percent were males and 43 percent females, 84 percent were Caucasian and 16 percent Negro. Lesions confined to or originating in the antrum made up 67 percent while non‐antral lesions were 33 percent. Mean age at diagnosis was 59.1 years. Smoking and drinking history did not appear to be contributory. Antral lesions were retrospectively staged according to Sisson's TNM classification. Sixteen tumor typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
2

Year Published

1980
1980
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(35 citation statements)
references
References 7 publications
1
32
2
Order By: Relevance
“…The difference was highly significant in the log-rank analysis, as suggested in previous reports. 17,66,76,95,96,104,111,134,135,139,154,167,169,180 The meta-analysis confirmed that surgery (70%) and combined surgery and radiation (56%) offer better local control and cure rates than radiotherapy alone (33%). Most series, including ours, are biased in patient selection, and no randomized study has been published.…”
Section: Treatment Modalitymentioning
confidence: 64%
See 1 more Smart Citation
“…The difference was highly significant in the log-rank analysis, as suggested in previous reports. 17,66,76,95,96,104,111,134,135,139,154,167,169,180 The meta-analysis confirmed that surgery (70%) and combined surgery and radiation (56%) offer better local control and cure rates than radiotherapy alone (33%). Most series, including ours, are biased in patient selection, and no randomized study has been published.…”
Section: Treatment Modalitymentioning
confidence: 64%
“…This was noted in previous articles on patients with primary tumors of the maxillary sinus. 5,90,92,95,104,117,126,137,144,154,155,157,162,173 Our 5-year CSAS rates were 91%, 64%, 70%, and 50% for patients with T1, T2, T3, and T4 tumors, respectively. These results are close to the meta-analysis data from the 1990s for patients with T1 tumors (94%) and T2 tumors (55%), but they are much better compared with the results for patients with T3 tumors (50%) and T4 tumors (27%).…”
Section: T Classificationmentioning
confidence: 99%
“…Prior reviews 1,2 suggest that certain presenting symptoms, such as unilateral pain, swelling, numbness, epistaxis, diplopia, and decreased vision, are more common in patients with sinonasal malignant neoplasm. Certain findings on CT scans may also be suggestive of etiology.…”
Section: Discussionmentioning
confidence: 98%
“…[15][16][17][18][19][20][21][22][23][24][25][26] We identified 5 cases of carcinosarcoma that originated in the maxillary sinus or ethmoid sinus with extension into the orbit. 15,16,19,23,26 These cases are summarized in Table 2.…”
Section: Discussionmentioning
confidence: 99%